Prehospital Emergency Service Use for Substance-Related Issues before and during COVID-19 - Esra Kabadayi Sahin; Eren Usul (Emergency Medicine International)
Objective. The COVID-19 pandemic disrupted the healthcare system and disproportionally affected individuals with substance use. This study aimed to evaluate the prehospital emergency medical service (EMS) use for substance-related health issues during the COVID-19 pandemic period and compare the changes with the pre-COVID-19 period. Methods. The prehospital EMS calls due to substance-related problems in overall Turkiye were analyzed retrospectively. The applications were categorized into the pre-COVID-19 period (May 11, 2019, to March 11, 2020) and the COVID-19 period (March 11, 2020, to January 4, 2021). These two periods were compared to if there were any changes in sociodemographic features of the applicants, the reason for EMS calls, and the dispatch results of the calls. Results. There were 6,191 calls in the pre-COVID-19 period and 4,758 calls in the COVID-19 period. According to the age groups, the number of applications of 18 years and under decreased, while the application of people 65 years and over increased during the COVID-19 period (p<0.001). Considering the reasons for the EMS application, there was an increase in the calls due to suicide and transfers during the COVID-19 period. Besides, the EMS applications for court-ordered treatment decreased in the COVID-19 period (p<0.001). There was no statistically significant difference in terms of dispatch results (p=0.081). Conclusions. This study shows that the elderly group is at higher risk for substance-related medical problems. Suicide is an important risk among individuals with substance use. The increase in demand for ambulance transfer services can place a significant burden on prehospital emergency care. There is a need for measures to provide emergency and transport services, especially for the elderly and suicide attempts during any future case of emergency.